Magnetic excitations in La$_{1.5}$Sr$_{0.5}$CoO$_4$ - Helme, L; Boothroyd, A; Prabhakaran, D; Wondre, F; Frost, C; Kulda, J (2003)
We report magnetization and neutron scattering measurements of the half-doped compound La$_{1.5}$Sr$_{0.5}$CoO$_4$, which exhibits a checkerboard pattern of charge ordering below ~800K. In the antiferromagnetically-ordered phase below \~40K the spins are found to be canted in the ab plane. The spin excitation spectrum includes spin-wave excitations with a maximum energy of 16 meV, and diffuse magnetic modes at energies around 30 meV.